THE RELATIONSHIP BETWEEN COMFORT AND PERFORMANCE IN FR PROTECTION CLOTHING - Malagó, Larissa Stephanie de Souza; Alfieri, Paulo Pedro Maria; Borelli, Camilla (Seven Editora, 2025)
This article investigates the relationship between comfort and mechanical performance in FR protection garments, considering the physiological and tactile impacts of the use of this equipment in the industrial environment. From the characterization of three fabrics with different flame retardant technologies, tests were carried out according to ASTM, AATCC and ISO standards to evaluate mechanical performance (abrasion and tearing) and comfort (physical and thermophysiological). The fabric with inherent FR fibers achieved the best results in terms of comfort and durability. As a novelty, the study proposes a critical discussion based on the international literature and presents suggestions for methodological advancement for future research.DOI: https://doi.org/10.56238/sevened2025.021-009